Optimally diversified portfolio - Deannes Isynuwardhana (STIE Perbanas Surabaya, 2014)
Investors can reduce risk by diversification or by forming a portfolio from its investment so that the possibility of the loss from one stock can be covered by gaining from other stock. One of the problems encountered in the formation of the portfolio is related to the size of the portfolio itself, is about how many stock in the portfolio that will minimize the level of risk. This research was conducted to determine the relationship between the size of the portfolio and risk level, both in total risk (variance) and unsystematic risk. By using Blue Chip stock in April 2012 as the sample period, the portfolio size range will be calculated for the level of risk, as result the number of stock in the portfolio that will produce the lowest level of risk. The result of this research showed that the greater the number of stocks in the portfolio will provide a level of lower unsystematic risk, meaning that the size of a large portfolio showed a good level of diversification. Optimally diversified portfolio consists of approximately 16 stocks, while over 16 stocks the level of unsystematic risk is decreased but not significant. This suggests that the size of the portfolio has a negativerelationship with the level of unsystematic risk.